GE_GERICHTE C/22361/2013 vom 29. September 2014 - GE Cour de justice (2014)
BAIL À LOYER; RÉSILIATION; APPEL(CPC); CONDITION DE RECEVABILITÉ; VALEUR LITIGIEUSE; CONSORITÉ; BAIL COMMUN; MOTIF; SOUS-LOCATION | CPC.70; CC.162